Understanding the Meaning-Making of Romantic Relationships among Emerging Adults after Parental Divorce - Carissa Azarine Delicia; Nida Ul Hasanat (Faculty of Psychology, Universitas Gadjah Mada, 2022)
Pursuing a romantic relationship is one of the most important developmental aspects of emerging adults. With the increasing divorce rate in Indonesia, the authors were interested in exploring how emerging adults make sense of romantic relationships after parental divorce. Three participants and two significant others were interviewed in this present study, in which interpretive phenomenological analysis was used as the approach to interpreting the data. This study generated two themes that show how emerging adults make meaning of romantic relationships, namely as a source of fear and a source of support. This contradictory meaning-making relates to the experience the participants had during their parents' divorce process and what they learned from the media or their significant others. These, coupled with human agency and the need for love, encourage the participants to learn from their parents' mistakes, develop certain behavioural patterns, and continue to seek romantic relationships in their lives. This study shows how interaction between parents during a divorce process can shape the meaning-making and behaviour patterns in the child’s romantic relationships. Therefore, it is suggested that divorced parents build an open communication, show positive interactions, and minimize exposing their children to negative interactions during the divorce process.